Selective and Accurate Determination Method of Propofol in Human Plasma by Mixed-Mode Cation Exchange Cartridge and GC-MS - Jae Sung Pyo (Journal of Analytical Methods in Chemistry)
A gas chromatography-mass spectrometry (GC-MS) method for the determination of propofol in human plasma has been developed and validated. Propofol was extracted from human plasma by using mixed-mode cation exchange/reversed-phase (MCX) cartridges. As propofol easily volatilizes during concentration, 100% methanol was injected directly into GC-MS to elute propofol. Despite avoiding concentration process of the eluted solution, lower limit of quantization (LLOQ) of propofol was 25 ng/mL. The validated method exhibited good linearity (R2=0.9989) with accuracy and precision −5.8%~11.7% and 3.7%~11.6%, respectively. The other validation parameters, recovery and matrix effect, ranged from 96.6% to 99.4% and 95.3% to 101.4%, respectively. Propofol standard was quantified to evaluate possible loss due to the concentration processes, nitrogen gas and centrifugal vacuum. These two concentration processes resulted in notable decrease in the quantity of propofol, signifying avoiding any concentration processes during propofol quantification. Also, to confirm suitability of the developed method, authentic human plasma samples were analyzed. The selective assay method using MCX cartridge and GC-MS facilitated quantification of propofol in plasma sample accurately by preventing any losses due to the concentration processes.